Continuous-wave operation of (Al, In)GaN distributed-feedback laser diodes with high-order notched gratings. (3rd October 2018) - Slight, Thomas J.; Stanczyk, Szymon; Watson, Scott; Yadav, Amit; Grzanka, Szymon; Rafailov, Edik; Perlin, Piotr; Najda, Stephen P.; Leszczyński, Mike; Gwyn, Steffan; Kelly, Anthony E.
Abstract: We report on the continuous-wave, room-temperature operation of a distributed-feedback laser diode (DFB-LD) with high-order notched gratings. The design, fabrication, and characterization of DFB devices, which are based on the (Al, In)GaN material system, is described. The uncoated devices exhibited single-wavelength emission at 408.6 nm with an optical power of 20 mW at 225 mA. A side-mode suppression ratio (SMSR) of 35 dB was achieved, with a resolution-limited full-width at half maximum of 6.5 pm.